THE IMPORTANCE OF LEADERSHIP FOR ENTERPRISE COMPETITIVENESS IMPROVEMENT - Mitrović, Vladimir; Mitrović, Ivana (Ekonomija - teorija i praksa, 2021)
The position of Serbian economy in relation to developed economies in the world is still not on the satisfactory level. Yearly competitiveness report clearly indicates that Serbia, without clear and radical changes, will not be able to successfully compete with the competition from wider and immediate surroundings. The aim of this paper is to show and explain how Serbia, in order to improve its position in relation to other countries, needs leaders who are able to manage radical changes, leaders who can define the direction and course of the reforms, at the same time instilling trust, inspiring and motivating people for them. Both enterprises and all kinds of organizations will have to adapt and change quickly or they will not be able to survive in the ever-changing environment, as it is today and as it will be in the future.